Calidad de servicio y satisfacción del cliente en el Albergue Amazon Curassow Lodge & Expeditions S.R.L. de la ciudad de Iquitos, 2024 - Arista Aspajo, Astrid Antuane (2025)
Title: Quality of Service and Customer Satisfaction at Amazon Curassow Lodge & Expeditions S.R.L. Hostel in Iquitos City, 2024. The objective: To determine the relationship between service quality and customer satisfaction at the Amazon Curassow Lodge & Expeditions S.R.L. Lodge, in the city of Iquitos, 2024. Methodology: correlational, descriptive, non-experimental design research. The sample: 186 clients of the Hostel participated. Results: It was determined that the quality of service in its reliability dimension is linked to satisfaction in its dimension: expectation and empathy (p=0.000 and p=0.000 respectively). Responsiveness is related to perception (p=0.015), and security is related to perception (p=0.027). Trustworthiness is not significant for perception, responsiveness is not significant for expectation and empathy. Likewise, security is not significant for expectation or empathy. It is concluded that there is no relationship between the quality of service and customer satisfaction at the Amazon Curassow Lodge & Expeditions S.R.L. Lodge, in the city of Iquitos, (p=0.136)